2014
DOI: 10.1371/journal.pone.0093451
|View full text |Cite
|
Sign up to set email alerts
|

Designing a High-Throughput Somatic Mutation Profiling Panel Specifically for Gynaecological Cancers

Abstract: Somatic mutations play a major role in tumour initiation and progression. The mutation status of a tumour may predict prognosis and guide targeted therapies. The majority of techniques to study oncogenic mutations require high quality and quantity DNA or are analytically challenging. Mass-spectrometry based mutation analysis however is a relatively simple and high-throughput method suitable for formalin-fixed, paraffin-embedded (FFPE) tumour material. Targeted gene panels using this technique have been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 41 publications
(52 reference statements)
2
39
1
Order By: Relevance
“…Konopka et al [33] however describe a weak correlation between PIK3CA mutations and higher tumour grade. KRAS mutations occurred in 35% of our samples, which is slightly higher than previously reported rates of 10–31% [16, 17, 20, 27, 28]. KRAS mutations were mainly detected in low FIGO stage and endometrioid carcinomas (type I tumours).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Konopka et al [33] however describe a weak correlation between PIK3CA mutations and higher tumour grade. KRAS mutations occurred in 35% of our samples, which is slightly higher than previously reported rates of 10–31% [16, 17, 20, 27, 28]. KRAS mutations were mainly detected in low FIGO stage and endometrioid carcinomas (type I tumours).…”
Section: Discussioncontrasting
confidence: 68%
“…In a large study of Spaans et al [20], PIK3CA , PTEN , and KRAS were found the most frequently occurring mutations in gynaecological carcinomas in 22, 18 and 12%, respectively. This is comparable with the results of our study where 40, 30, and 25% of tumours harboured a PTEN , KRAS , or PIK3CA mutation, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 This gene panel only covers 40% of PTEN mutations found in endometrial cancer and therefore loss of PTEN protein expression was analyzed by immunohistochemistry. Mutations in POLE exons 9 and 13, which together contain 490% of the pathogenic POLE exonuclease domain mutations, were detected by using Sanger sequencing.…”
Section: Mutation Analysismentioning
confidence: 99%
“…A number of previous studies have demonstrated that mutations in the kinases of the RAS/RAF/MEK/ERK transduction pathway are frequently observed in human cancer, including cervical carcinoma (5)(6)(7)(8). Of these, V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS p.G12, p.G13 and p.Q61), neuroblastoma RAS (NRAS; p.G12, p.G13 and p.Q61), Harvey RAS (HRAS; p.G12, p.G13 and p.Q61) and B-Raf proto-oncogene serine/threonine kinase (BRAF; p.V600E) mutations were among the most typically observed and were considered to be hotspot mutations in these genes (6,9,10).…”
Section: Introductionmentioning
confidence: 99%